Prediction of Moisture Content of Natural Gases Using Simple Arrhenius-type Function - Bahadori, Alireza (Versita, 2011)
Natural gas extracted from underground reservoirs is saturated with water. The accurate prediction of moisture content in natural gas is extremely important. The presence of water vapor can lead to potentially disastrous consequences. The lifetime of a pipeline is governed by the rate at which corrosion occurs, which is directly linked to the available moisture in the gas resulting in oxidation. In addition, the formation of hydrates due to presence of water in natural gas can lead to safety hazards to production/transportation systems and to substantial economic risks. In this paper, an attempt has been made to develop an easy-to-use Arrhenius-type asymptotic exponential function combined with the Vandermonde matrix to arrive at an appropriate estimation of saturated water content of sour natural gases for pressures up to 69000 kPa and the temperature range between 20 to 180°C. Percent average absolute deviation of the proposed method is found to be around 2%, demonstrating the excellent performance of the developed predictive tool. The tool will be of great practical value for chemical and petroleum engineers to have a quick check on the water content of sour natural gases at various temperatures and pressures without performing any experimental measurements.